Effect of Promotional Strategy on Consumer Interest in Online Shopping at Shopee (Case Study on Students of the Faculty of Economics and Business Unismuh Makassar Management Study Program Class of 2018). - Aris Pasigai; Alisa Amanda Fitri (Jurnal Ilmu Manajemen Profitability, 2024)
The purpose of this research is a quantitative type of research with the aim of knowing the effect of promotional strategies on consumer interest in shopping online at shopee (a case study on students of the Faculty of Economics and Business, Unismuh Makassar, Management Study Program class of 2018). The sample in this study amounted to 76 respondents. Data was collected by observing and distributing questionnaires. In this study, the data sources used in data collection include primary data. The research instrument used in this study used the Likert scale method. Based on the results of data research using statistical calculations through the Statistical Package for Social Science (SPSS) version 25 application regarding the effect of promotional strategies on consumer interest in online shopping at shopee (a case study on students of the Faculty of Economics and Business, Unismuh Makassar, 2018 Management Study Program) which has been discussed from the previous chapter, the authors draw an important conclusion, namely the promotion strategy has a positive and significant effect on consumer interest.